2023
DOI: 10.1002/adom.202301057
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Energy Transfer from Monolayer WS2 to Organic Dye Molecules: Conversion of Faint Visible‐Red into Bright Near‐Infrared Luminescence

Abstract: The synergetic combination of transition metal dichalcogenides (TMDCs) with organic dye molecules in functional heterostructures is promising for various optoelectronic applications. Here resonance energy transfer (RET) from a red‐emitting WS2 monolayer (1L‐WS2) to a layer of near‐infrared (NIR) emitting organic dye molecules is demonstrated. It is found that the total photoluminescence (PL) yield of the heterostructures is up to a factor of eight higher as compared to the PL yield of pristine 1L‐WS2. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…14,139 Further, resonance energy transfer (RET) from a red-emitting WS 2 monolayer (1L-WS 2 ) to a layer of near-infrared (NIR)emitting organic dye molecule-based type I heterostructures is demonstrated. 29 It is found that the total PL yield of the heterostructures is up to a factor of eight higher than the PL yield of pristine 1L-WS 2 . They have explained that the efficient RET alone is necessary but not sufficient for the desired PL enhancement.…”
Section: Strong Optical Response In Tmdomentioning
confidence: 90%
See 1 more Smart Citation
“…14,139 Further, resonance energy transfer (RET) from a red-emitting WS 2 monolayer (1L-WS 2 ) to a layer of near-infrared (NIR)emitting organic dye molecule-based type I heterostructures is demonstrated. 29 It is found that the total PL yield of the heterostructures is up to a factor of eight higher than the PL yield of pristine 1L-WS 2 . They have explained that the efficient RET alone is necessary but not sufficient for the desired PL enhancement.…”
Section: Strong Optical Response In Tmdomentioning
confidence: 90%
“…For example, a resonance energy transfer (RET) from a red-emitting monolayer WS 2 (1L-WS 2 ) to a layer of NIR-emitting organic dye molecule–based type-I heterostructure. 29 It is found that the total PL yield of the heterostructures is up to a factor of eight higher than the PL yield of pristine 1L-WS 2 . A strong decrease in the PL of the dye is observed on 2L-WS 2 when it gives the type II heterostructure.…”
Section: Introductionmentioning
confidence: 90%